The relationship between cervical lordosis and neck pain: A systematic review and meta-analysis - Kim, Kyung-Ho; Park, Seong-Ah; An, Chang-Sik; Kim, Jeong-Lae (Edelweiss Applied Science and Technology, 2024)
: The interpretation of the correlation between cervical lordotic angle (CLA) and neck pain (NP) among clinicians remains contentious, reflecting the nuanced nature of this association within clinical discourse. This relationship assumes paramount importance in clinical practice, as it serves as the cornerstone for devising effective therapeutic strategies aimed at the management and prevention of NP. The objective of this study was to determine the difference in CLA between individuals with and without NP. The inclusion criteria entailed observational studies rigorously evaluating CLA through radiological imaging in both NP patients and healthy controls (HC), while pediatric, geriatric populations, and non-degenerative spinal conditions were excluded. We conducted a thorough electronic search across several databases including Medline, Cochrane Library, Embase, CINAHL, and PEDro. The search strategy employed terms pertinent to cervical alignment and NP, using Boolean logic. Specifically, search terms such as "neck pain*", "cervical pain*", and "lordo*" were used to ensure comprehensive coverage of relevant literature. We estimated the standardized Mean Differences (SMD) and their corresponding 95% Confidence Intervals (CI). Additionally, chi-square and I2 statistics were used to evaluate within-group heterogeneity through a random effects model. A total of 6 studies, involving 436 patients with NP and 491 HC, were identified. Overall, individuals with NP demonstrated a tendency towards smaller CLA compared to the HC group.